Chrześcijański hip-hop w służbie nowej ewangelizacji - KAMIŃSKA, MARTA (Annales Missiologici Posnanienses, 2010)
This article presents an attempt to show the “Christian” version of hip-hop or rap music. Even though at the beginning this kind of music was anti-Christian and this might be still in the mainstream, there are however some attempts of creating such a kind of music with an attitude of searching for deeper meaning in life and finding it sometimes in Christian life. Very important in this process was an audience, which John Paul II gave to the artists of this kind of music, somehow confirming that such music also might be used for evangelization.